2021
DOI: 10.13057/biodiv/d220302
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic characters, genetic and phenotypic diversity coefficients, and heritability of 12 genotypes of rice

Abstract: Abstract. Kartahadimaja J, Utomo SD, Yuliadi E, Salam AK, Warsono, Wahyudi A. 2021. Agronomic characters, genetic and phenotypic diversity coefficients, and heritability of 12 genotypes of rice. Biodiversitas 22: 1091-1097. The achievement of national rice production is always below the target. One of the causes is the low productivity of the varieties grown due to the stagnant genetic capacity of these varieties. The assembly of new lines through breeding is one solution that can increase the genetic capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…The coefficient of genotypic variation (GCV) and the coefficient of phenotypic variation (PCV) are very useful in determining the amount of diversity that exists in the population and are the basis for variability criteria (Mustikarini et al 2019;Saidon et al 2020). All traits showed high PCV than GCV, similar to the results reported by Srivastava et al (2017); Tiruneh et al (2021), indicating that the variance observed for the traits was more influenced by the genetic factors and suitable environment support the expression of genetic (Kartahadimaja et al 2021). A notable difference in PCV and GCV values indicates a significant environmental influence positively on the traits.…”
Section: Genetic Variability and Heritability Of Agronomic Traitssupporting
confidence: 76%
“…The coefficient of genotypic variation (GCV) and the coefficient of phenotypic variation (PCV) are very useful in determining the amount of diversity that exists in the population and are the basis for variability criteria (Mustikarini et al 2019;Saidon et al 2020). All traits showed high PCV than GCV, similar to the results reported by Srivastava et al (2017); Tiruneh et al (2021), indicating that the variance observed for the traits was more influenced by the genetic factors and suitable environment support the expression of genetic (Kartahadimaja et al 2021). A notable difference in PCV and GCV values indicates a significant environmental influence positively on the traits.…”
Section: Genetic Variability and Heritability Of Agronomic Traitssupporting
confidence: 76%
“…Based on the data analysis, the traits observed in each line showed a different effect in each line. Compared to another study, research by Kartahadimaja et al (2021) reported that statistical analysis of agronomic traits in 12 (twelve) rice genotypes showed that plant height, number of tillers, number of productive tillers, flag leaf width, flag leaf length, and flag leaf angle showed significant variation. Meanwhile, Kasim et al (2020) showed that the rice plant height of the 17 rice varieties ranged from 95-160 cm.…”
Section: Agronomic Traits Of the Linesmentioning
confidence: 59%
“…The same reference also stated that the shape of the rice grain is one of the determinants of rice grain quality. Grain quality is one of the selection parameters in plant breeding programs (Kush and Cruz 2000;Kartahadimaja et al 2021). Compared with the same line in the previous study (Oktaviani et al 2021), the dehulled rice size of F7 lines did not significantly differ from the F6 ones.…”
Section: Morpho-biochemical Profile Of the Linesmentioning
confidence: 80%
See 1 more Smart Citation
“…Morphological information, for plant breeders, is not only used to see the morphological similarities between the watermelon plants tested, but also to obtain genetic information about the relationship between the watermelon plants tested (Gichimu et al 2009). In the assembly of varieties, information on the relationship between breeding materials plays an important role in the efficient selection of parents through plant breeding programs (Choudhary et al 2012;Kartahadimaja et al 2021). Breeding materials with distant relatives are needed to determine the parents of the cross to assemble the desired variety (Gbotto et al 2016).…”
Section: Introductionmentioning
confidence: 99%